Mapping Wetlands of Kenya Using Geographic Resources Analysis Support System (GRASS GIS) with Remote Sensing Data - (:unkn) unknown (My University, 2023)
Monitoring wetlands of Kenya is critical for analysis of environmental changes since they present unique ecosystems with special hydrological balance and biodiversity. In this study, the Landsat 8-9 OLI/TIRS satellite images for 2015-2022 were classified using GRASS GIS scripts to evaluate changes in the Lorian Swamp wetland, northeastern Kenya. The results of the image analysis presented maps of land cover changes including wetlands. The study demonstrated technical effectiveness of the GRASS GIS for image analysis, and contributed to the environmental monitoring of African wetlands.
Keywords: African Research